English Professors’ Use of ICTs within Moroccan Higher Education Institutions - Laâbidi Hicham (Faculty of Arts and Humanities, Saïs-Fez, 2018)
Like several countries, Morocco has undertaken many educational reforms in order to upgrade the quality of education provided for students to help them face the challenges of the twenty first century. One of the major components of the last educational reform was the introduction of Information and Communication Technologies(ICTs) for pedagogical purposes. This shows that Moroccan educational policy-makers have grasped the importance of using computer technologies in teaching and learning processes. Indeed, ICTs has proved to be beneficial for both teachers and students. It boosts students’ motivation and increases their learning achievements. It also promotes teachers’ classroom performance and helps them develop professionally. The current study explors the integration of computer technologies by professors of English language within Moroccan higher education institutions. It examines the various factors that may influence their willingness to implement ICTs in the classroom. A survey questionnaire and a semi-structured interview were employed to collect the required data to answer the seven research questions guiding this research study. The data was analyzed using both descriptive and inferential statistics. The findings revealed that though professors of English language possesses positive attitudes towards the implementation of the new technologies in teaching, the levels of ICTs use for instructional objectives in their classrooms is low. It was found that this lack of computer technology integration in higher education institutions is attributed to the existence of several barriers. The most identified barriers that hinder professors use of information technologies are lack of technological infrastructure, lack of teachers’ computer skills, lack of suitable computer training, lack of administrative support , lack of time, lack of technical support , lack of internet connectivity, and lack of rewards and incentives. Actually, the results of this mixed-methods study can be used to develop appropriate strategies to enhance technology vi integration in education because it provides many recommendations to educational policy makers, administrators, as well as researchers.
Keywords: Langue et Littérature Anglaise; English Professors’ Use; Moroccan Higher Education Institution